Development and Feasibility of a BME 280 Sensor-Based Practicum Tool for Boyle–Gay-Lussac Law Experiments - Sagita, Elsa; Hartini, Tri Isti (Universitas Muhammadiyah Makassar, 2025)
The integration of sensor-based technology into physics learning is essential in the context of the Industrial Revolution 4.0, particularly for improving practicum-based conceptual understanding. This study aims to evaluate the effectiveness and feasibility of a Boyle–Gay-Lussac Law practicum tool developed using the BME280 sensor, which is capable of measuring pressure, temperature, and humidity simultaneously. The research adopted a Research and Development (RD) approach based on the Jan van den Akker model, involving preliminary research, prototyping, validation by experts, and small-scale field testing. Data were collected through Likert-scale questionnaires validated by physics education experts and tested among high school students. Media validation results achieved an average score of 93.6%, and material validation scored 78%, indicating excellent and good quality, respectively. Small-scale trials yielded average scores of 87.84% for media and 87% for material, categorized as excellent. The developed tool facilitated real-time experimentation, improved measurement accuracy, and enhanced student engagement and conceptual understanding of gas laws. The novelty of this tool lies in its integration of a multi-function sensor and real-time LCD display, offering a compact, reusable, and interactive practicum experience. Conclusions indicate that the BME280 sensor-based tool is both effective and feasible for physics instruction. This innovation contributes to physics education by modernizing practicum resources, promoting active learning, and bridging the gap between abstract thermodynamic concepts and practical experimentation.